Involvement of autophagy in MHC class I antigen presentation - Øynebråten, Inger (Scand J Immunol, 2020)
MHC class I molecules on the cellular surface display peptides that either derive from endogenous proteins (self or viral), or from endocytosis of molecules, dying cells or pathogens. The conventional antigen‐processing pathway for MHC class I presentation depends on proteasome‐mediated degradation of the protein followed by transporter associated with antigen‐processing (TAP)‐mediated transport of the generated peptides into the endoplasmic reticulum (ER). Here, peptides are loaded onto MHC I molecules before transportation to the cell surface. However, several alternative mechanisms have emerged. These include TAP‐independent mechanisms, the vacuolar pathway and involvement of autophagy. Autophagy is a cell intrinsic recycling system. It also functions as a defence mechanism that removes pathogens and damaged endocytic compartments from the cytosol. Therefore, it appears likely that autophagy would intersect with the MHC class I presentation pathway to alarm CD8(+) T cells of an ongoing intracellular infection. However, the importance of autophagy as a source of antigen for presentation on MHC I molecules remains to be defined. Here, original research papers which suggest involvement of autophagy in MHC I antigen presentation are reviewed. The antigens are from herpesvirus, cytomegalovirus and chlamydia. The studies point towards autophagy as important in MHC class I presentation of endogenous proteins during conditions of immune evasion. Because autophagy is a regulated process which is induced upon activation of, for example, pattern recognition receptors (PRRs), it will be crucial to use relevant stimulatory conditions together with primary cells when aiming to confirm the importance of autophagy in MHC class I antigen presentation in future studies.